2012
DOI: 10.1900/rds.2012.9.148
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Mechanisms in Type 1 Diabetes: The Islet is Both Target and Driver of Disease

Abstract: Recent advances in our understanding of the pathogenesis of type 1 diabetes have occurred in all steps of the disease. This review outlines the pathogenic mechanisms utilized by the immune system to mediate destruction of the pancreatic beta-cells. The autoimmune response against beta-cells appears to begin in the pancreatic lymph node where T cells, which have escaped negative selection in the thymus, first meet beta-cell antigens presented by dendritic cells. Proinsulin is an important antigen in early diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 155 publications
(285 reference statements)
0
57
0
Order By: Relevance
“…This severe depletion of intra-islet beta-cells suggests that beta-cells during early development are more susceptible to autoimmune destruction and that islets are the primary target as well as the driver of the disease (24). Beta-cells during development and growth (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This severe depletion of intra-islet beta-cells suggests that beta-cells during early development are more susceptible to autoimmune destruction and that islets are the primary target as well as the driver of the disease (24). Beta-cells during development and growth (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis revealed that HLA-A2-restricted CD8 + T cells specific for islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP), GAD-65, preproislet amyloid polypeptide, and preproinsulin were present in this donor's islets. It is believed that HLA class I-restricted CD8 + T cells that recognize b-cell autoantigens are responsible for b-cell destruction (34). In the NOD mouse model, spreading of the CD8 + immune response from proinsulin to IGRP only requires CD4 + T cells specific for proinsulin (11), which could also be the case in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in cytotoxic effector cells can be interpreted concerning Graham et al. 's and Faustman's findings [15,16].…”
Section: Discussionmentioning
confidence: 99%